A internacionalização de empresas brasileiras para Angola: desafios e oportunidades - Pinheiro, Tiago Grégoire de Souza (2016)
The aim of this work is to analyze the internationalization of Brazilian companies in Angola. Despite the difficulties, there are numerous opportunities for Brazilian companies. This study was based on the theories of institutional gaps, specific advantages of the firm (FSA) and specific advantages of the country of origin (CSA), and the state's role in the internationalization of companies. The study sample consisted of interviews with 12 experts from Brazil-Angola relations. Research results indicate that the Brazilian companies to Angola to have well-defined competitive advantage and, in most cases, go to the African country aimed at exploring the local institutional gaps. However, the perception of the actors involved, Brazilian companies are going to explore institutional gaps, taking advantage of their competitive advantages, they are not supported efficiently by the Brazilian state. Thus, lack a state policy that prioritizes these companies. The findings also indicate that to succeed in business in Angola, it is essential to build partnerships with local actors such as entrepreneurs and especially the government. In this context, a strategic roadmap is suggested to assist Brazilian companies operating in the African country.